Transcriptional regulation of basic fibroblast growth factor gene by p53 in human glioblastoma and hepatocellular carcinoma cells. - Ueba, T (1994)
Mutations of the p53 gene are found in various human cancers. The frequency of its mutation is reported to increase during tumor progression in most tumors. In human gliomas, mutations of the p53 gene are found in about one-third of the malignant forms and in few of the benign ones, indicating their possible involvement in tumor progression. On the other hand, we have recently shown that basic fibroblast growth factor (basic FGF) plays a crucial role in tumor progression as an autocrine growth factor in tissues of human gliomas. Therefore, we hypothesized that p53 might regulate the promoter activity of the basic FGF gene, which has several GC boxes and no typical TATA box. In this study, cotransfection assays using human glioblastoma and hepatocellular carcinoma cells and establishment of stable cell lines expressing mutant-type p53 were performed. The basic FGF gene promoter was demonstrated to be regulated by p53 at the transcriptional level and its basal core promoter was found to be responsive to p53. Expression of endogenous basic FGF was also demonstrated to be activated by mutant type p53. Wild-type p53 repressed gene expression of the basic FGF and its mutant activated it in vitro, implying one of the possible pathways in tumor progression.